Pyrosequencing analysis of bacterial community changes in dental unit waterlines after chlorogenic acid treatment - Li, Na; Cai, Qin-Ming; Hu, Ni-Ya; Jiang, Shu-ling; Chen, Fu-Qing; Hu, Qiao-Qiao; Yang, Fen; He, Chao-Zhu (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction The contamination of dental unit waterlines (DUWLs) poses a significant risk of cross-infection in dentistry. Although chemical disinfectants have been effective in reducing number of bacteria, they do have limitations. Methods This study aimed to investigate the potential of chlorogenic acid, a natural substance with broadspectrum antibacterial properties, for treating DUWLs. Over a period of three months, we analyzed the microbial communities in 149 DUWLs samples collected from 5 dental units using high-throughput pyrophosphate sequencing. Results The results revealed that chlorogenic acid treatment had a significant impact on the microbial community profile in the DUWLs, with the most significant changes occurring within the first 15 days and stabilization observed in the last 30 days. The predominant genera detected in the samples were Bacteroides, Lactobacillus, Streptococcus, Methylobacterium, and Phreatobacter. Additionally, the relative abundance of certain beneficial bacteria, such as Alloprevotella, Roseburia, and Blautia, increased, while the presence of opportunistic pathogens like Mycobacteria significantly decreased. The functional prediction analysis using the KEGG database indicated a decrease in the pathogenicity of the bacterial community in the DUWLs following chlorogenic acid treatment. Discussion This study introduces a novel approach for the prevention and treatment of infections associated with dental care.